Congenital hepatoblastoma presenting with hepatic arteriovenous fistulas: a case report - Jiao Lin; Jialing Guo; Chun Chen; Liqiong Jiang; Can Lai; Chunlin Wang (Frontiers Media S.A., 2023)
AimCongenital hepatoblastoma, a rare malignant liver tumor in infancy, typically presents with abdominal distension or mass. Tumors detected antenatally or during the first three months of age are considered congenital hepatoblastoma. Hepatic arteriovenous fistulas (HAVF) are associated with high mortality in the neonatal period and can be caused by many secondary factors. This case report focuses on a patient with congenital hepatoblastoma accompanied by HAVF, highlighting the clinical and imaging characteristics and management strategies.Case presentationA term infant presented with sudden tachypnea and heart failure on his first day of life. A cystic-solid mixed lesion in the fetus's liver was detected by an antenatal ultrasound scan. Postnatal digital subtraction angiography confirmed the presence of arteriovenous fistulas, which were treated with trans-arterial embolization. However, despite the intervention, the patient's heart failure did not improve. The patient underwent a left hepatectomy, and hepatoblastoma was discovered by histology of the resected hepatic lobe. Unfortunately, metastases were later discovered in the intracranial and ocular regions. Ultimately, the family decided to discontinue further treatment.ConclusionCongenital hepatoblastoma presenting with hepatic arteriovenous fistulas has not been previously described. Hepatoblastoma should be considered when alpha-fetoprotein levels show a significant elevation in newborns. Prenatal diagnosis may improve pre- and postnatal management.